Development of a remote electronic tongue system combined with the VMD-HT feature extraction method for honey botanical origin authentication. (February 2021) - Yin, Tingjia; Yang, Zhengwei; Miao, Nan; Zhang, Xin; Li, Qingsheng; Wang, Zhiqiang; Li, Caihong; Sun, Xia; Lan, Yubin
Graphical abstract: Highlights: Authentication of honey form its botanical origin is achieved by electronic tongue. A novel remote electronic tongue system is developed and applied. A new feature extraction method is used for analyzing electronic tongue signals. The approach may be used as an on-site tool for honey authentication. Abstract: The misrepresentation of honey botanical origin causes serious economic losses for honey producers and consumers. In this work, a novel remote electronic tongue system was developed and utilized to identify honey from different botanical origins. The system mainly comprises an electrode array, a portable instrument, a general packet radio service (GPRS) transmitter module, and a remote server. To reduce the number of redundant variables, a feature extraction method combining variational mode decomposition and Hilbert transformation (VMD-HT) is proposed. Then, the classification algorithm, principal component analysis (PCA) and extreme learning machine (ELM) are applied to discriminate different honey samples. The experiments show that the proposed method obtains more accurate classification results than other existing feature extraction methods. The developed electronic tongue system provides a rapid, portable and cost-effective method for honey botanical origin authentication, which can be effectively applied in the honey industry.